A Review of Research Progress on Separation and Purification Methods of Lithium Isotopes Using Cation Exchange Resin and Their Applications - Yilong SONG; Min LIU; Kejun HOU (Yankuang ceshi)
Lithium (Li) isotopes serve as effective geochemical tracers in mantle-crust cycling, planetary evolution, climate change, continental weathering, mineralization mechanisms, and environmental pollution studies. Efficient separation of lithium from natural samples is essential due to potential interference from isobaric isotopes during analysis. Over the past decades, cation exchange resin methods have been developed to enhance lithium separation for TIMS and MC-ICP-MS analysis. Since then, these methods have evolved to reduce blank contamination, simplify procedures, improve efficiency, and expand applicability to various natural samples. This review examines recent advances in Li isotope separation using single-column, double-column, multi-column and in-series column methods. Key factors like resin type, eluent volume, and method efficiency for various samples are discussed. Single- and double-column methods dominate current research, of which some methods just use minimal resin and eluent while controlling process blanks to below 0.1‰. However, separation efficiency remains dependent on lithium content and matrix ions in the sample. Further optimization is needed to balance efficiency, cost, and applicability across sample types. As analytical techniques advance, automated elution systems are likely to become central to Li isotope analysis. The BRIEF REPORT is available for this paper at http://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.202409050181.